Monetary Policy and Public Finances : Inflation Targets in a New Perspective - Beddies, Christian (IMF Working Papers; Working Paper, 1999)
This paper considers the interaction between the private sector, the monetary authority, and the fiscal authority, and concludes that unrestricted central bank independence may not be an optimal way to collect seigniorage revenues or stabilize supply shocks. Moreover, the paper shows that the implementation of an optimal inflation target results in optimal shares of government finances-seigniorage, taxes, and the spending shortfall-from society's point of view but still involves suboptimal stabilization. Even if price stability is the sole central bank objective, a positive inflation target has important implications for the government's finances, as well as for stabilization.